Design of a Yoruba Language Speech Corpus for the Purposes of Text-to-Speech (TTS) Synthesis - Aoga, John O.R.; FANOU, CODJO CHARLEMAGNE; DAGBA, Théophile Komlan (My University, 2016)
This paper deals with the design of a speech corpus for a corpus-based Text-To-Speech (TTS) synthesis approach. The purposes are first to provide enough speech to develop Yoruba corpus-based TTS system and second, to provide a simple methodology for other languages corpus design. The paper focuses on text analysis, selection of the reliable sentences, selection of the reader, and sentences recording. The analysis is performed to ensure a good balance of the corpus. Then, 2,415 sentences are gathered (essentially affirmative sentences). Those sentences have been read by a Yoruba language journalist who is a native speaker of the language. There is one speaker for the whole corpus
Keywords: Yoruba language; Language corpus; TTS; Unit selection